THE STUDY OPPORTUNITIES OF SELF-OSCILLATIONS IN THE SYSTEM OF AUTOMATIC REGULATION OF THE VOLTAGE OF THE RINGS CONTROL WITH RELAY CONTROLLER BASED ON POWER KEY - Biluhin, D. S. (Science and Transport Progress, 2009)
The possibility of application of the modern power semiconductor keys is considered for realization of asynchronous method of control of voltage level for circuits of on-board feeding of electric locomotives.